Moving in extreme environments: extreme loading; carriage versus distance. Issue 1 (December 2016) - Lucas, Samuel; Helge, Jørn; Schütz, Uwe; Goldman, Ralph; Cotter, James
Abstract This review addresses human capacity for movement in the context of extreme loading and with it the combined effects of metabolic, biomechanical and gravitational stress on the human body. This topic encompasses extreme duration, as occurs in ultra-endurance competitions (e.g. adventure racing and transcontinental races) and expeditions (e.g. polar crossings), to the more gravitationally limited load carriage (e.g. in the military context). Juxtaposed to these circumstances is the extreme metabolic and mechanical unloading associated with space travel, prolonged bedrest and sedentary lifestyle, which may be at least as problematic, and are therefore included as a reference, e.g. when considering exposure, dangers and (mal)adaptations. As per the other reviews in this series, we describe the nature of the stress and the associated consequences; illustrate relevant regulations, including why and how they are set; present the pros and cons for self versus prescribed acute and chronic exposure; describe humans' (mal)adaptations; and finally suggest future directions for practice and research. In summary, we describe adaptation patterns that are often U or J shaped and that over time minimal or no load carriage decreases the global load carrying capacity and eventually leads to severe adverse effects and manifest disease under minimal absolute but high relative loads. We advocate that further understanding of load carrying capacity and the inherent mechanisms leading to adverse effects may advantageously be studied in this perspective. With improved access to insightful and portable technologies, there are some exciting possibilities to explore these questions in this context.